A 3‐year follow‐up study on the risk of stroke among patients with conjunctival haemorrhage. (9th March 2012) - Wang, Tsung‐Jen; Keller, Joseph J.; Sheu, Jau‐Jiuan; Lin, Herng‐Ching
Abstract. Purpose: To the best of our knowledge, no large population‐based studies on the relationship between conjunctival haemorrhage and stroke have been conducted to date. Using a nationwide population‐based data set, this study investigated the relationship between conjunctival haemorrhage and the subsequent risk of stroke within a 3‐year period following diagnosis. Methods: We analysed data sourced from the Taiwan Longitudinal Health Insurance Database 2000. The study cohort consisted of 17 349 patients with conjunctival haemorrhage and 86 745 comparison subjects. Each patient was individually tracked for a 3‐year period from their index date to identify all those who had subsequently received a diagnosis of stroke. Results: The incidence rate of stroke was 2.44 (95% CI = 2.31–2.55) per 100 person‐years in patients with conjunctival haemorrhage and 1.63 (95% CI = 1.59–1.68) per 100 person‐years in comparison patients. After adjusting for patients' monthly income and geographic location, as well as for hypertension, atrial fibrillation, diabetes, hyperlipidaemia and coronary heart disease, stratified Cox proportional hazards regressions revealed a statistically significant hazard ratio for stroke in patients with conjunctival haemorrhage (HR = 1.33; 95% CI = 1.24–1.42, p < 0.001). Conclusions: In this study, patients with conjunctival haemorrhage were found to be at a significant risk of stroke during a 3‐year follow‐up period after diagnosis.